1993
DOI: 10.1021/jm00058a003
|View full text |Cite
|
Sign up to set email alerts
|

Centrally acting serotonergic agents. Synthesis and structure-activity relationships of C-1- or C-3-substituted derivatives of 8-hydroxy-2-(di-n-propylamino)tetralin

Abstract: The synthesis and structure-activity relationships (SAR) of C-1- or C-3-substituted derivatives of 8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT) are described. These analogs were synthesized via alkylation of the tetralone derivatives followed by reductive amination. All of the analogs were inactive at the dopamine D2 receptor. Among the 8-OMe or 8-OH C-1,N-disubstituted analogs synthesized, the cis analogs were more potent in the 5-HT1A binding assay than the corresponding trans analogs. However, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…(1S,2R)-3: R1=H, R2=CH3 (1S,2fl)-4: R'=R2=CH3 8-Hydroxy-2-(dipropylamino)tetralin (8-OH-DPAT; 2), which was reported by Arvidsson et al5 to be a potent centrally active 5-HT-receptor agonist, is a selective 5-HTiA-receptor ligand.6-8 It has served as a lead compound in the search for compounds with similar indirect models which describe observed structureactivity relationships (SAR) have been deduced. [12][13][14][15] One of the key derivatives in our indirect model for 5-HTiA-receptor agonists13 was the potent agonist (lS,2R)-ALK-3 [(lS,2R)-3]. 16 Compound QS,2fl)-3 has a limited conformational flexibility as compared to 2, 12 and the selectivity and high 5-HTiA-receptor affinity of 2 appeared to be retained in (l,S,2R)-3.16 '17 A more detailed pharmacological evaluation has demonstrated that (lS,2R)-3 may be best characterized as a partial 5-HTiA-receptor agonist.17 Similarly, (S)-2 appears to be a partial 5-HTiA-receptor agonist, whereas (R)-2 behaves as a full agonist.17 In contrast to the enantiomers of 2, which display little stereoselectivity, 18 (lS,2R)-3 behaves as a potent 5-HTiA-receptor agonist in ex vivo biochemical and behavioral tests, whereas the l.R,2iS-enantiomer is inactive.…”
Section: Introductionmentioning
confidence: 99%
“…(1S,2R)-3: R1=H, R2=CH3 (1S,2fl)-4: R'=R2=CH3 8-Hydroxy-2-(dipropylamino)tetralin (8-OH-DPAT; 2), which was reported by Arvidsson et al5 to be a potent centrally active 5-HT-receptor agonist, is a selective 5-HTiA-receptor ligand.6-8 It has served as a lead compound in the search for compounds with similar indirect models which describe observed structureactivity relationships (SAR) have been deduced. [12][13][14][15] One of the key derivatives in our indirect model for 5-HTiA-receptor agonists13 was the potent agonist (lS,2R)-ALK-3 [(lS,2R)-3]. 16 Compound QS,2fl)-3 has a limited conformational flexibility as compared to 2, 12 and the selectivity and high 5-HTiA-receptor affinity of 2 appeared to be retained in (l,S,2R)-3.16 '17 A more detailed pharmacological evaluation has demonstrated that (lS,2R)-3 may be best characterized as a partial 5-HTiA-receptor agonist.17 Similarly, (S)-2 appears to be a partial 5-HTiA-receptor agonist, whereas (R)-2 behaves as a full agonist.17 In contrast to the enantiomers of 2, which display little stereoselectivity, 18 (lS,2R)-3 behaves as a potent 5-HTiA-receptor agonist in ex vivo biochemical and behavioral tests, whereas the l.R,2iS-enantiomer is inactive.…”
Section: Introductionmentioning
confidence: 99%
“…The less polar product (4.09 g, 58.9%) was obtained as an oil. Conversion into the HCI salt and recrystallization afforded (±)-7a as a white solid: *H NMR 7.18-7.10 (m, 4 H), 6.42-5.44 (m, 3 ), 4.10-1.60 (m, 12 The more polar product (0.4 g, 5.8%) was also obtained as an oil. Conversion into the HCI salt and recrystallization afforded (±)-8a as a white solid: The assignment of the major product (±)-7a as the cis isomer and the minor product (±)-8a as the trans isomer was based on the cts-lactam as the major component in the starting material 6a.…”
Section: Methodsmentioning
confidence: 99%
“…3 ), 4.18-1.90 (m, 12 ), irans-(±)-2,3,3a,4,5,9b-Hexahydro-6-methoxy-3-(cyclopropylmethyl)-l/f-benz[e]indole Hydrochloride (8e). This compound was prepared from trans-(±)-6e (0.48 g, 1.8 mmol), using the reduction procedure described in the preparation of (±)-7a and (±)-8a.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diester was then treated with potassium tert-butoxide in Et 2 O, and the precipitated potassium salt was filtered, dried and then decarboxylated using a DMSO/H 2 O/LiCl reagent system. 30,31 The H 2 O was added in the form of concentrated HCl to neutralize the potassium salt from the previous reaction. The 2-tetralone was purified as its bisulfite adduct, which upon treatment with sodium carbonate liberated to the ketone.…”
mentioning
confidence: 99%